Self Balancing Inverted Pendulum Robot - Kast, Jacob (My University, 2014)
The purpose of this study was directed toward developing an autonomous self-balancing robot. In order for the robot to balance, it must have a sensor system to indicate its angle of tilt to the vertical.
Color poster with text and images.
Keywords: Autonomous robots; Self-balancing; Posters